Considering the Arabian Neolithic through a reconstitution of interregional obsidian distribution patterns in the region. (18th April 2013) - Khalidi, Lamya; Inizan, Marie‐Louise; Gratuze, Bernard; Crassard, Rémy
Abstract : As a result of a programme devoted to obsidian geochemical analyses for the Red Sea region (VAPOR), the register of analysed obsidian artefacts from Arabia has grown considerably in recent years. A percentage of these correspond to surveyed and excavated Neolithic contexts in Yemen, Saudi Arabia and Oman. This growing database of site to source matches has enabled us to consider the Neolithic of Arabia as more than just a period of sedentism and initial domestication, but as a period where we can begin piecing together the formulation of complex social networks and exchange mechanisms that included, and may even have depended to some extent on, mobile groups. Using obsidian source analyses coupled with spatial mapping, site and lithic data, we use obsidian as a guide to gain a better understanding of the early dynamics of interaction between regions in Arabia and beyond, and to assess what role the socio‐economic networks identified may have had in the process of Arabian Neolithisation, or in certain cases, the lack thereof.